Bitter Panicgrass, Bitter Panicum, Panicum amarum - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Bitter panicgrass is important in dune stabilization and building and often grows intermixed with sea oats on foredunes. It is also found spread throughout back dunes, interdunal swales, and coastal grasslands. This plant occurs throughout coastal Florida, except for the Big Bend coast, west to New Mexico, and along coastal northeast states to Massachusetts. A significant proportion of bitter panicgrass reproduction is by vegetative spread; its seeds are often sterile. https://edis.ifas.ufl.edu/sg178